Micro-grids Applications, Operation, Control and Protection - Ghofrani, Mahmoud (IntechOpen, 2019)
The integration of recent and emerging energy technologies in the existing electric grid requires modifications in several aspects of the grid, including its architecture, protection, operation, and control. Micro-grid provides a solution for integrating distributed energy resources such as renewable energy generation, energy storage systems, electric vehicles, controllable loads, etc. and delivers flexibility, security, and reliability by operating in both grid-connected and isolated modes. This book provides an overview of micro-grid solutions, applications, and implementations. State-of-the-art methods for micro-grid operation, optimization, and control are presented. Distributed energy resources and their interactions in micro-grids are also studied. In addition, micro-grid designs, architectures, and standards are covered, as are micro-grid protection strategies and schemes for different operation modes.